The Use of Virtual Reality Experiences to Aid the Reduction of Workplace Stress - Patel, Ash (Digital Repository of Theses - SSBM Geneva, 2025)
The world economy, and in direct connection, society relies on millions of people around the world to work. Work in the context of industrial, commercial, retail, governmental, and other settings. The workforce, made up of varying demographics, experiences, and competencies, relies on physical, and mental well-being to perform. It is shown that workplace-related health issues are costly for a number of reasons as outlined in this report. As a particularly important aspect of workforce health, mental health has often been unrecognized, and not addressed appropriately. Specifically, this research study focuses on workplace stress, as defined throughout the content, and qualified through the literature review. Stress, as recognized as a predicator to anxiety. Workplace stress, whether it is a direct result of occupational activities, or domestic oriented, has costly consequences, such as reduced productivity, turnover, health care cost increases, conflicts, and degradation of innovation. This research study is purposed for the testing of the use of virtual reality experiences to aid in the mitigation of workplace stress. Through the process, the nature of stress experienced, and reactions to the exposure to virtual reality are defined. Attitudes, and perceptions of participants are correlated to their reporting of the success of the experiences. This research study is particularly important to establish evidence of the efficacy of one, non-traditional, method to mitigate workplace stress. This, in turn, will open the potential for wider research into the effectiveness of virtual reality experiences to achieve stated results, and the outlining of a framework for evolution of their production. The researcher has selected this topic because of a passionate connection to workplace stress, and his association with virtual reality experience production. The researcher has the determination to validate the effective outcomes of combining the two areas of interest.